Clinical outcomes of chikungunya: A systematic literature review and meta-analysis. - Kris Rama; Adrianne M de Roo; Timon Louwsma; Hinko S Hofstra; Gabriel S Gurgel do Amaral; Gerard T Vondeling; Maarten J Postma; Roel D Freriks (Public Library of Science (PLoS), 2024)
Background Chikungunya is a viral disease caused by a mosquito-borne alphavirus. The acute phase of the disease includes symptoms such as fever and arthralgia and lasts 7-10 days. However, debilitating symptoms can persist for months or years. Despite the substantial impact of this disease, a comprehensive assessment of its clinical picture is currently lacking. Methods We conducted a systematic literature review on the clinical manifestations of chikungunya, their prevalence and duration, and related hospitalization. Embase and MEDLINE were searched with no time restrictions. Subsequently, meta-analyses were conducted to quantify pooled estimates on clinical outcomes, the symptomatic rate, the mortality rate, and the hospitalization rate. The pooling of effects was conducted using the inverse-variance weighting methods and generalized linear mixed effects models, with measures of heterogeneity reported. Results The systematic literature review identified 316 articles. Out of the 28 outcomes of interest, we were able to conduct 11 meta-analyses. The most prevalent symptoms during the acute phase included arthralgia in 90% of cases (95% CI: 83-94%), and fever in 88% of cases (95% CI: 85-90%). Upon employing broader inclusion criteria, the overall symptomatic rate was 75% (95% CI: 63-84%), the chronicity rate was 44% (95% CI: 31-57%), and the mortality rate was 0.3% (95% CI: 0.1-0.7%). The heterogeneity between subpopulations was more than 92% for most outcomes. We were not able to estimate all predefined outcomes, highlighting the existing data gap. Conclusion Chikungunya is an emerging public health concern. Consequently, a thorough understanding of the clinical burden of this disease is necessary. Our study highlighted the substantial clinical burden of chikungunya in the acute phase and a potentially long-lasting chronic phase. Understanding this enables health authorities and healthcare professionals to effectively recognize and address the associated symptoms and raise awareness in society.